Pengaruh Lama Fermentasi Terhadap Mutu Biji Kakao (Theobroma cacao L) yang dihasilkan Petani Kakao Di Teluk Kedondong Bayur Samarinda - Marwati - (PROSIDING SEMINAR KIMIA, 2013)
Cocoa is one of the plantation commodity whose have role in the national economy, particularly as a provider of employment and sources of income for the government. In addition, The cacao bean is also improved the incomes of cocoa farmers especially to cocoa farmer at Teluk Kedondong Bayur, Samarinda. Cocoa production in Indonesia increased significantly, but the quality of the resulting is very low. The purpose of this study to determine how long fermentation time to produce good quality of cocoa beans.Single factor experiment in completely randomized design (CRD) with three replications times used in this study. The factor variation is length of fermentation which consists of seven standards: no fermentation, 1 day, 2 days, 3 days, 4 days, 5 days, and 6 days. Data were analyzed using analysis of variance (ANOVA) with F test, if there is a real difference it will be followed by Least Significant Difference Test (BNT) with level of 5%. Result of the experiment showed that treatment with long fermentation gave significantly effect on moisture content, pH, fat content, number of seeds per 100 grams, not fermented beans levels, levels of seed germination and yield. Based on the results of testing of dry beans, the best quality treatment withfermentation time is 5 days.